Effects of Non-verbal Priming on Attachment-Style Activation - Sim, Suhyung; Shin, Ji-eun; Sohn, Young Woo (Frontiers in Psychology, 2019)
Using an affective priming procedure, two experiments examined the effects of non-verbal cues on activating attachment styles. In Study 1, the secure attachment group, which was primed non-verbally, showed higher levels of self-esteem, interpersonal competence, and positive affect than the insecure attachment group, which was also primed non-verbally. In contrast, no significant difference was found between the two attachment groups that were primed verbally. In Study 2, using a different priming method and adding a neutral group, similar interactions between priming modality (non-verbal or verbal cues) and attachment styles were found: the differences in self-esteem, interpersonal competence, and positive affect between the secure attachment group, neutral group, and insecure attachment group were greater when primed non-verbally than when primed verbally. Finally, the limitations of the research and recommendations for follow-up study are discussed.